Comparison of PET/CT and MRI in the Diagnosis of Bone Metastasis in Prostate Cancer Patients: A Network Analysis of Diagnostic Studies - Liu, Fanxiao; Dong, Jinlei; Shen, Yelong; Yun, Canhua; Wang, Ruixiao; Wang, Ganggang; Tan, Jiyang; Wang, Tao; Yao, Qun; Wang, Bomin; Li, Lianxin; Mi, Jingyi; et al. (Frontiers in Oncology, 2021)
Abstract: Background: Accurate diagnosis of bone metastasis status of prostate cancer (PCa) is becoming increasingly more important in guiding local and systemic treatment. Positron emission tomography/computed tomography (PET/CT) and magnetic resonance imaging (MRI) have increasingly been utilised globally to assess the bone metastases in PCa. Our meta-analysis, a high-volume series compared the utility of PET/CT with different contrast agents and MRI with different parameters in this setting. Materials and Methods: Evidence acquisition: Three databases, including the Medline, Embase and Cochrane Library, were searched to retrieve original trials from their inception to 31 August 2019 according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) statement. The methodological quality of the included studies was assessed by two independent investigators utilizing QUADAS-2. A Bayesian network meta-analysis was performed using an arm-based model. Absolute sensitivity and specificity, relative sensitivity and specificity, diagnostic odds ratio (DOR) and superiority index and their associated 95% confidence intervals (CI) were used to assess the diagnostic value. Results: Forty-five studies with 2843 patients and 4263 lesions were identified. Network meta-analysis reveals that 68Ga-labelled prostate membrane antigen (68Ga-PSMA) PET/CT has the highest superiority index (7.30) with the sensitivity of 0.91 and specificity of 0.99, followed by 18F-NaF, 11C-choline, 18F-choline, 18F-Fludeoxyglucose (FDG) and 18F-fluciclovine PET/CT. The use of high magnetic field strength, multi-sequence, DWI, more imaging panels will increase the diagnostic value of MRI for the detection of bone metastasis in prostate cancer patients. Where available, the performance of 3.0-T high-quality MRI approaches 68Ga-PSMA PET/CT in the detection of bone metastasis on patient-based level (sensitivity: 0.94 vs. 0.91; specificity: 0.94 vs. 0.96, superiority index: 4.43 vs. 4.56). Conclusions: 68Ga-PSMA PET/CT is recommended for the diagnosis of bone metastasis in prostate cancer patients. Where available, the performance of 3.0-T high-quality MRI approaches 68Ga-PSMA PET/CT in the detection of bone metastasis.